Analisis Fraud Pentagon terhadap 4 Perusahaan yang Terdeteksi Melakukan Kecurangan Laporan Keuangan - Ghaizky Ara Bahar; Temy Setiawan (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The company will have a good quality of financial reports if the company have 5 qualitative characteristics of financial statements, namely: relevant, comparable, reliable, and understandable. The quality of company’s financial statements will decrease if it doesn’t have these characteristics. With poor quality financial statements, there’s the possibility of fraudulent financial statement. Financial statement fraud is an action taken by changing material value in the financial statements, so it doesn’t show the company’s actual conditions. This study aims to prove that the fraud pentagon theory is able to detect fraudulent financial statements by applying it to 4 cases of companies that were detected to commit fraudulent financial statements in Indonesia. This study uses 12 indicators with a qualitative research using case studies, descriptive and comparative analysis. The object of the research is annual report of company under study. The selected cases of fraudulent financial statement are PT Tiga Pilar Sejahtera Tbk, PT Garuda Indonesia Tbk, PT Hanson International Tbk, PT Bank Bukopin Tbk. The study was conducted by comparing the results of the calculation trough the company’s annual report. The results showed that Financial targets, Financial stability, Nature of industry, and Company existence were able to detect fraudulent financial statements. Meanwhile, External pressure, Ineffective monitoring, Quality of external audit, change in auditor, audit reports, change in director, change in age, number of CEO’s picture were not able to detect fraudulent financial statements.